Comparing elbow injury risks in collegiate softball and baseball athletes: previous involvement in softball versus baseball - Yuka Tsukahara, Erika Jyoto, Rie Sato (Research in Sports Medicine, 2025)
Overhead throwing sports, such as baseball and softball, pose a risk of upper extremity injuries, including the elbow. Studies on overhead throwing sports among female athletes is scarce compared to their male counterparts. A total of 329 athletes (271 softball, 58 baseball) aged 18-22 years participated in the study and answered an anonymous survey regarding their personal backgrounds and elbow injuries. The most common diagnosis among the 61 athletes who reported having elbow injuries diagnosed by a physician was ulnar collateral ligament injuries (29.5%). In addition, a total of 15.5% of athletes did not seek medical attention from a physician despite experiencing discomfort in their elbow, with time constraints being the most common reason. Athletes engaged in competitive baseball before college had a significantly elevated likelihood of experiencing elbow injuries and discomfort compared to those who engaged in non-overhead throwing sports (Odds ratio = 3.84, 95% CI 1.16-12.72, p = 0.028) but engaging in softball prior to college was not a significant risk factor for sustaining elbow injuries. Playing competitive baseball prior to college emerged as a risk factor for sustaining elbow injuries among Japanese female collegiate softball and baseball athletes.